2010
DOI: 10.1051/0004-6361/201014912
|View full text |Cite
|
Sign up to set email alerts
|

Dark energy domination in the Virgocentric flow

Abstract: Context. The standard ΛCDM cosmological model implies that all celestial bodies are embedded in a perfectly uniform dark energy background, represented by Einstein's cosmological constant, and experience its repulsive antigravity action. Aims. Can dark energy have strong dynamical effects on small cosmic scales as well as globally? Continuing our efforts to clarify this question, we now focus on the Virgo Cluster and the flow of expansion around it. Methods. We interpret the Hubble diagram from a new database … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 49 publications
(86 reference statements)
5
20
0
Order By: Relevance
“…We have previously (Chernin et al 2007a) discussed the data for the dwarf galaxies around the Local Group. The distance data come mainly from high accuracy observations of the TRGB (Tip of the Red Giant Branch) using the Hubble Space Telescope as reported by Karachentsev and his team in a series of papers (references e.g.…”
Section: The Hubble Diagram For the Group Environmentsmentioning
confidence: 99%
“…We have previously (Chernin et al 2007a) discussed the data for the dwarf galaxies around the Local Group. The distance data come mainly from high accuracy observations of the TRGB (Tip of the Red Giant Branch) using the Hubble Space Telescope as reported by Karachentsev and his team in a series of papers (references e.g.…”
Section: The Hubble Diagram For the Group Environmentsmentioning
confidence: 99%
“…, it is nevertheless receding at 1004 ± 70 km·s −1 [97]. Only galaxies within 9 ~ 11 Mpc have any realistic chance of eventually merging with it.…”
Section: Discussionmentioning
confidence: 97%
“…Equation (109) was the argument given by Chernin et al (2010) to solve the Hubble-Sandage paradox on the scale of ∼10 Mpc (Sandage 1986(Sandage , 1999 observed that the local expansion was similar to that due to the Hubble flow. In the case of a shell i, its proper velocity at t t Fig.…”
Section: Discussionmentioning
confidence: 99%